Prevalence of Venereophobia among Patients of Non-Venereal Genital Conditions- a Cross-Sectional Hospital Based Study from Nepal - Vikash Paudel; Deepa Chudal; Upama Paudel; Dwarika Prasad Shrestha (Nepal Journal of Dermatology, Venereology & Leprology)
Background